Racial Discrimination and University Students’ Mental Health: a Cross-Sectional Study - Naila Khan; Andrea Kaifie (Journal of Racial and Ethnic Health Disparities, 2026)
Abstract Background Racial discrimination is associated with negative mental health outcomes among students, yet it remains understudied at German universities. Methods In a period of two months in 2022 a cross-sectional study was conducted at a German university using an anonymous bilingual online questionnaire for data collection. Results Among 179 students who had experienced racial discrimination in their lives, 106 (59.2%) reported it at their university. Students and teaching staff were the most frequently reported aggressors. International students were identified to be especially vulnerable. The study group displayed high average scores in the Patient Health Questionnaire (PHQ): 8.1 (SD = 5.9) for anxious, 10.0 (SD = 6.8) for depressive and 8.9 (SD = 6.2) for somatic symptoms. At least moderate symptom severity (score ≥ 10) for anxiety, depression and somatization was found in 31.7%, 47.0% and 40.5% respectively. For anxiety, a score ≥ 10 was significantly more prevalent in the group that experienced racial discrimination at university compared to the group that did not (41.8% vs. 18.9%) ( p < 0.05). Comparable differences were found for somatization symptoms (53.8% vs. 23.5%) ( p < 0.01). Regarding depression, a similar trend was observed (54.5% vs. 37.3%), though not statistically significant ( p = 0.06). Conclusion The findings imply that experiencing racial discrimination in university is associated with higher levels of anxiety and somatization with a similar trend for depression. As this research field remains understudied, further qualitative and longitudinal research is required.